AB1295 Ultrasound assessment at patients with late onset of rheumatoid arthritis: Higher scores of inflammation activity of joint compared to early onset of rheumatoid arthritis. (23rd January 2014) - Osipyants, R.; Panasyuk, E.; Karateev, D.; Gluchova, S.; Aleksandrova, E.; Volkov, A.
Abstract : Background: Growing evidence supports the hypothesis that in elderly onset of rheumatoid arthritis (RA) patients (pts) showed higher sonographic scores of inflammation despite similar clinical disease activity compared to in young onset of RA. Objectives: To evaluate inflammatory changes of joints by grey scale (GS) ultrasonography (US) at pts with late and early onset of RA. To compare US findings with clinical and laboratory data. Methods: Twenty-one pts (76% women) with RA were enrolled. All pts were divided into two groups: 1st (n=11) – pts with early onset of RA (before the age of 55 years), 2nd (n=10) – with late onset of disease (after the age of 55 years). US examination (``Voluson-i" (GE, USA), 4-13MHz probe) was included the GSUS scores of the wrists and hands: the US scores in 24 joints (bilateral wrist and hand) - US24; in dominated hand - 8 (wrist (2), II-IV MCP and II-IV PIP) - US8 and 5 joints (wrist, II-III MCP and II-III PIP) - US5. Different semiquantitative synovitis sum scores were generated by GS results. On the same day, laboratory data (CRP, ESR), clinical disease activity (28 tender/swollen joints, disease activity score-28 (DAS28), clinical disease activity index (CDAI) and simplified disease activity index (SDAI)) were evaluated. Results: Ten pts with late onset of RA [median age 65 (range 63-67) years; disease duration 36 (12-48) months; DAS28 6.6 (5.6-7.2); 70% "+" for rheumatoid factor (RF) and 80% "+" for anti-citrullinated peptide antibodies (ACCP))] and eleven pts with early onset of disease [48 (39-53) years; 60 (24-96) months; DAS28 6.8 (5.9-7.1); 91% "+" for RF, 80% "+" for ACCP)]. Pts with late onset of RA had higher the US scores from the 24, 8, 5 joints vs. pts with early onset of RA [26.5 (19-32) vs. 16 (13-18) for US24, p=0.026; 12 (8-13) vs. 7 (5-10) for US8, p=0.048; 8.5 (6-10) vs. 5 (3-6) for US5, p=0.022]. Interestingly, a level of RF (titer) in pts with early onset of disease was higher compared to the other group [279 (205-665) vs. 113 (9.5-215), p=0.029]. The laboratory markers of inflammation as well as parameters of clinical disease activity were comparable between both groups of pts. Conclusions: RA pts with onset of disease after the age of 55 years showed high US scores of inflammation despite laboratory data and clinical disease activity. Consequently, it is possible more rapid subclinical disease progression compared to pts with early onset of RA. Disclosure of Interest: None Declared